The Development of Spermatophyte E-Catalog in Hutan Kota Salatiga as Learning Resource on Plantae Material for Senior High School Students - Jati, Anis Lina; Ngabekti, Sri (FMIPA UNNES, 2021)
This study aims to identify species richness of spermatophytes in Hutan Kota Salatiga, develop the e-catalog, analyze the validity, readability, and effectiveness of spermatophyte e-catalog as a learning resource on plantae material for senior high school students. The research method used in this study is Research and Development (R&D). The spermatophyte e-catalog was validated by media and material expert. Small-scale trials were used to test the readability and effectiveness of the product. The readability test involved one biology teacher and 10 students from class X MIPA 1, while the effectiveness test involved 20 students from class X MIPA 1. Both data validity, readability, and effectiveness were analyzed by descriptive percentage. The results of plant exploration show that there are 58 spermatophyte species in the Hutan Kota Salatiga. The validity of spermatophyte e-catalog obtained score 91,25% from material expert and 95,83% from media expert, with very valid criteria. The readability of spermatophyte e-catalog obtained score 85% from biology teacher and 89,83% from students, with very good criteria. The results of the effectiveness test show that spermatophyte e-catalog was effectively used as a learning resource with score of the classical completeness criteria reaches 95%. Based on the results of this study, it can be concluded that the Spermatophyte E-Catalog of Hutan Kota Salatiga feasible and effective to be used as a learning resource on plantae material for senior high school students.